Study of oxidative stress in osteoarthritis And rheumatoid arthritis - DR. SMITA PADHY,; DR.HIMANSHU SEKHAR DASH, (International Journal of Pharma and Bio Sciences, 2017)
Osteoarthritis is one of the most common age-related degenerative joint disorders. Rheumatoid arthritis is an autoimmune inflammatory disease of the joints affecting 1% of world wide population. The present study was undertaken to evaluate the status of oxidative stress marker (lipid peroxidation) and antioxidants level in Osteoarthritis and Rheumatoid arthritis. The study was conducted by taking 50 Osteoarthritis patients, 50 Rheumatoid arthritis patients and 50 healthy individuals (controls)in Hi-Tech medical college and hospital, Bhubaneswar. Levels of lipid peroxidation marker (malondialdehyde) and antioxidants like superoxide dismutase, vitamin E, vitamin C were measured in all the study groups. Significant increase in malondialdehyde was found in both Osteoarthritis and Rheumatoid arthritis as compared to controls showing evidence of oxidative stress in this diseases. Significant increase in superoxide dismutase activity was found in both Osteoarthritis and Rheumatoid arthritis might be an adaptive response. Significant decrease in vitamin E, vitamin C was found in Osteoarthritis and Rheumatoid arthritis showing impaired activity of antioxidant system. Therefore, antioxidants therapy will be beneficial in this disease.